Teaching in inclusive classrooms: efficacy and beliefs of Canadian preservice teachers. Issue 1 (2nd January 2016) - Specht, Jacqueline; McGhie-Richmond, Donna; Loreman, Tim; Mirenda, Pat; Bennett, Sheila; Gallagher, Tiffany; Young, Gabrielle; Metsala, Jamie; Aylward, Lynn; Katz, Jennifer; Lyons, Wanda; Thompson, Scott; et al.
Abstract : This study provides a Canada-wide snapshot of the self-efficacy and beliefs of 1490 preservice teachers in relation to inclusive teaching using the Teacher Efficacy for Inclusive Practice and the Beliefs about Learning and Teaching Questionnaire. At the time of data collection, these preservice teachers were in the final stages of their teacher education programmes. Based on the results of surveys in 11 Faculties of Education, men have higher self-efficacy than women for managing behaviour in the classroom, elementary preservice teachers have higher self-efficacy in collaboration than those teaching in secondary schools, those enrolled in the 1-year post-degree programme show lower self-efficacy than those enrolled in programmes of other durations, and those who have experience with people with special education needs show higher self-efficacy than those who do not. Differences illustrated that women were more inclusive than men, 1-year post-degree preservice teachers were less inclusive than others, and those who have experience with people with special education needs are more inclusive than those who do not. Recommendations for teacher education and limitations surrounding the practical significance of the findings are discussed.